On the numerical solution of fractional Schrodinger differential equations with the Dirichlet condition - Ashyralyev, Allaberen; Hicdurmaz, Betul (Taylor & Francis Ltd, 2012)
The first and second orders of accuracy difference schemes for the mixed problem for the multidimensional fractional Schrodinger differential equation with dependent coefficients are considered. Stability estimates for solutions of these difference schemes are obtained. Numerical methods are proposed for solving the one-dimensional fractional Schrodinger differential equation with Dirichlet condition in the space variable.
Keywords: difference scheme; fractional Schrodinger differential equation; Dirichlet condition; fractional differential equation; stability